2011
DOI: 10.1016/j.cell.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Signal Processing in Synthetic MAP Kinase Cascades

Abstract: SUMMARY The flexibility of MAPK cascade responses enables regulation of a vast array of cell-fate decisions, but elucidating the mechanisms underlying this plasticity is difficult in endogenous signaling networks. We constructed insulated mammalian MAPK cascades in yeast to explore how intrinsic and extrinsic perturbations affect the flexibility of these synthetic signaling modules. Contrary to biphasic dependence on scaffold concentration, we observe monotonic decreases in signal strength as scaffold concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
144
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 54 publications
2
144
0
Order By: Relevance
“…In recent years synthetic biology has greatly advanced the design of biomedical devices (19)(20)(21)(22) that provide new diagnostic tools (23); offer novel concepts for the treatment of cancer (24,25), immune diseases (26,27), and diabetes (28); and pioneered prosthetic networks as a therapy for hyperuricemic disorders such as the tumor lysis syndrome and gout (29). Still, all synthetic biology-based treatment strategies target a single disorder at a time, taking advantage of a specific therapeutic nucleic acid or protein compound.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years synthetic biology has greatly advanced the design of biomedical devices (19)(20)(21)(22) that provide new diagnostic tools (23); offer novel concepts for the treatment of cancer (24,25), immune diseases (26,27), and diabetes (28); and pioneered prosthetic networks as a therapy for hyperuricemic disorders such as the tumor lysis syndrome and gout (29). Still, all synthetic biology-based treatment strategies target a single disorder at a time, taking advantage of a specific therapeutic nucleic acid or protein compound.…”
Section: Discussionmentioning
confidence: 99%
“…The S. pombe pheromone MAPK module, like the mammalian Raf-MEK-ERK cascade, which can functionally replace it (Hughes et al 1993), lacks a scaffold protein. Interestingly, synthetic biological approaches have shown that a simple concentration increase of sequential Raf-MEK-ERK kinases is sufficient to lower the activation threshold and enhance ultrasensitivity, leading to full activation (O'Shaughnessy et al 2011). This evidence leads us to propose that the local concentration of the pheromone MAPK cascade at the fusion site in S. pombe represents a natural situation in which the cell exploits the ultrasensitivity of the MAPK cascade to convert it to the fully active state, which, due to the spatially restricted location in which this takes place, drives an essentially irreversible decision to fuse.…”
Section: Spatial Focalization Of Mapk Signaling As a Cellular Decisionmentioning
confidence: 99%
“…U nderstanding the information processing abilities of biological systems is a central problem for systems and synthetic biology (1)(2)(3)(4)(5)(6). The properties of a living system are often inferred from the observation of its response to static perturbations.…”
mentioning
confidence: 99%